2009
DOI: 10.1103/physrevb.80.174204
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneity and glass-forming ability in the bulk metallic glassPd42.5Ni7.5Cu30P

Abstract: Core-level photoemission spectroscopy and anomalous x-ray scattering ͑AXS͒ measurements were performed for the Pd 42.5 Ni 7.5 Cu 30 P 20 ͑PNCP͒ excellent metallic glass to investigate the chemical nature and local atomic structure, and the results were compared to those in Pd 40 Ni 40 P 20 and Pd 40 Cu 40 P 20 . The P 2p core levels clearly separate into two states, indicating that the P atoms have two different chemical sites, which is a strong experimental proof for the existence of an elastic inhomogeneity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 27 publications
7
28
2
Order By: Relevance
“…There, it was found that the Pd 4 d partial DOS largely decreases near the Fermi energy, EF, and its feature seems to become localized by replacing the Ni atoms with the Cu atoms, while that of the Ni partial DOS remains almost unchanged. Therefore, these electronic data demonstrate that these results are closely related to the excellent GFA of the PNCP bulk metallic glass through a selective formation of Pd–P covalent bonds .…”
Section: Introductionsupporting
confidence: 62%
“…There, it was found that the Pd 4 d partial DOS largely decreases near the Fermi energy, EF, and its feature seems to become localized by replacing the Ni atoms with the Cu atoms, while that of the Ni partial DOS remains almost unchanged. Therefore, these electronic data demonstrate that these results are closely related to the excellent GFA of the PNCP bulk metallic glass through a selective formation of Pd–P covalent bonds .…”
Section: Introductionsupporting
confidence: 62%
“…The above explanation was confirmed using the anomalous XRD by Park et al [227], who found different local structures around Ni and Cu, which can be explained by assuming that Cu is associated with the tetragonal dodecahedral packing, while Ni is associated with the TTP. The scenario of two different chemical environments around P was further supported in a P 2p core-level photoemission spectroscopy study of Pd 42.5 Cu 30 Ni 7.5 P 20 conducted by Hosokawa et al [228].…”
Section: Multicomponent Ltm-nm Metallic Glasses and Chemical Heterogementioning
confidence: 98%
“…A similar result was observed in polyalcohols by Dö et al 47 These findings suggest that shortening the chain structures could suppress b-relaxations (other possible reasons are also noted in Ngai et al 48 ). In Pd-Ni-Cu-P MG systems, several studies from the electronic and atomic structural perspectives have uncovered that with the increasing of Cu contents, the MGs acquire deeper binding energy and develop more covalent-like bonding, and especially chain-like Pd-P-Pd/Cu atomic configuration was suggested [49][50][51] . These findings are consistent with our observation that Cu promotes b-relaxations in Pd-Ni/Cu-P systems because of its strong interactions with Pd and P. In a Pd-Cu-Si MG, Bedorf and Samwer 45 studied the length-scale effects on relaxations and they found that by reducing the film thickness o30 nm, the b-relaxations are effectively suppressed.…”
Section: Discussionmentioning
confidence: 99%